1985
DOI: 10.1128/aac.28.6.815
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of UK-49,858 (fluconazole) against Candida albicans experimental infections in mice

Abstract: UK-49,858 (fluconazole), a new, orally absorbed bis-triazole derivative, has been evaluated against systemic infections with Candida albicans in normal and immunosuppressed mice and against an intestinal infection with C. albicans in immunosuppressed mice. Orally administered ketoconazole was used as a comparison agent throughout, and orally administered amphotericin B was included for comparative in the experimental intestinal infection. In a 10-day dosage regimen, UK-49,858 was far more active than ketoconaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
36
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 16 publications
5
36
0
Order By: Relevance
“…Viability studies of three isolates of Candida species exposed to fluconazole demonstrated that the drug was fungistatic and not fungicidal whether tested against the yeast in stationary or early logarithmic phase (144 Fluconazole is active in the treatment of experimental candidiasis as well. In normal and immunosuppressed mice, fluconazole administered for 10 days was found to be significantly more active than ketoconazole against systemic infections with C. albicans (308). In normal mice, fluconazole administered for 30 days prolonged survival of infected mice for >90 days, and up to 60% of the animals had no detectable C. albicans cells in their kidneys.…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 95%
“…Viability studies of three isolates of Candida species exposed to fluconazole demonstrated that the drug was fungistatic and not fungicidal whether tested against the yeast in stationary or early logarithmic phase (144 Fluconazole is active in the treatment of experimental candidiasis as well. In normal and immunosuppressed mice, fluconazole administered for 10 days was found to be significantly more active than ketoconazole against systemic infections with C. albicans (308). In normal mice, fluconazole administered for 30 days prolonged survival of infected mice for >90 days, and up to 60% of the animals had no detectable C. albicans cells in their kidneys.…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 95%
“…One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37). Recently, the antifungal efficacy of Flu was demonstrated in persistently granulocytopenic rabbits when it was used for prevention or early treatment (39,40).…”
mentioning
confidence: 99%
“…injection in treating normal AKR and C57BL/6 mice infected with Histoplasma capsulatum (7). Others have reported that fluconazole was more effective than the imidazole ketoconazole in treating normal mice (12,14) and rats (12,13) (14) reported that fluconazole was more than 20 times as effective as ketoconazole in C. albicans-infected mice that were immunocompromised by daily administration of dexamethasone. Fluconazole is an attractive antifungal agent in that (i) it is less toxic than amphotericin B, (ii) it is renally excreted, (iii) it readily penetrates cerebral spinal fluid, and (iv) it has a high serum half-life that can be maintained by daily oral administration (5).…”
mentioning
confidence: 99%